2022
DOI: 10.51253/pafmj.v72isuppl-2.3132
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Anti-Ganglioside Antibodies in Patients Diagnosed With Guillain Barre Syndrome

Abstract: Objective: To assess the frequency of patients positive for the presence of anti-ganglioside antibodies and factors related to it among the patients diagnosed with Guillian Barre Syndrome (GBS) at our hospital. Study Design: Prospective longitudinal study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from Jan to Jun 2019. Methodology: Patients were included in the study once detailed assessment and investigations have been carried out by the consultant neurologist a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In different studies, it was found that AIDP is the more prevalent variety of GBS in children. 3,4 Prolonged motor DL, reduced NCV, temporal dispersion and abnormal F-wave latency are characteristic electrophysiologic features of demyelination. 1 Although enough data of electrophysiological findings in adult GBS has been reported in literarturs, however, there was small data of electrophysiological findings in pediatric GBS particularly from Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…In different studies, it was found that AIDP is the more prevalent variety of GBS in children. 3,4 Prolonged motor DL, reduced NCV, temporal dispersion and abnormal F-wave latency are characteristic electrophysiologic features of demyelination. 1 Although enough data of electrophysiological findings in adult GBS has been reported in literarturs, however, there was small data of electrophysiological findings in pediatric GBS particularly from Pakistan.…”
Section: Introductionmentioning
confidence: 99%